2022
DOI: 10.1080/21655979.2022.2074770
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ZNFX1 antisense 1 (ZFAS1) suppresses anti-oxidative stress in chondrocytes during osteoarthritis by sponging microRNA-1323

Abstract: LncRNAs play a regulatory role in osteoarthritis (OA); however, the detailed mechanism remains to be elucidated. This study aimed to investigate the role of lncRNA zinc finger NFX1-type containing 1 (ZNFX1) antisense 1 (ZFAS1) in OA progression and explore its possible mechanismsagainst oxidative stress. Human cartilage specimens were obtained from 10 patients without OA who underwent traumatic amputation and 25 patients with OA who underwent total knee replacement surgery. Chondrocytes were prepared from harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Brusatol is a drug that inhibits Nrf2-mediated glucose metabolism ( 112 ). Gu’s team found that brusatol could partially abrogate the inhibitory effect of MiR-1323 on IncRNA ZFAS1 to promote chondrocyte proliferation and inhibit oxidative stress ( 113 ). This finding suggested that this compound may be a candidate drug for OA patients with reduced levels of IncRNA ZFAS1 expression.…”
Section: Lncrna-related Therapymentioning
confidence: 99%
“…Brusatol is a drug that inhibits Nrf2-mediated glucose metabolism ( 112 ). Gu’s team found that brusatol could partially abrogate the inhibitory effect of MiR-1323 on IncRNA ZFAS1 to promote chondrocyte proliferation and inhibit oxidative stress ( 113 ). This finding suggested that this compound may be a candidate drug for OA patients with reduced levels of IncRNA ZFAS1 expression.…”
Section: Lncrna-related Therapymentioning
confidence: 99%
“…But, a previous study indicated that ZFAS1 sponged miR-34b-5p to elevate the expression of sirtuin 1 (SIRT1), which alleviated inflammatory response in sepsis-induced myocardial injury [9]. Moreover, it was reported that ZFAS1 directly targeted miR-1323, which further repressed oxidative stress and inflammation in osteoarthritis [10]. These studies suggested its protective ability in inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA ZNFX1 antisense 1 (ZFAS1) reduced anti-oxidative stress via sponge of miR-1323 in osteoarthritis ( Gu et al, 2022 ). LncRNA PILA enhanced the activity of PRMT1 and activated NF-κB pathway in osteoarthritis ( Tang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%